Associations of circadian syndrome with gout and hyperuricemia: a cross‑sectional analysis of NHANES 2007–2018 - Jun-Wei Ren; Jia-Hao Wang; Yun-Fei Xiao; Yun-Jin Bai; Ping Han (BMC Public Health)
Abstract Background Gout and hyperuricemia, driven by elevated uric acid (UA). Circadian syndrome (CircS), a cluster of cardiometabolic risk factors related to circadian disruption, may interact with these conditions, but evidence remains limited. Understanding the potential associations of CircS with gout and hyperuricemia is crucial for effective health interventions. Objective To explore the associations of CircS with gout and hyperuricemia. Materials and methods This cross-sectional study utilized data from six National Health and Nutrition Examination Survey (NHANES) cycles (2007–2018). Participants aged ≥ 20 years with complete data on gout status, serum UA, and CircS were included. Gout was determined by self-reported physician diagnosis (questionnaire item MCQ160), and hyperuricemia was defined as serum UA > 7.0 mg/dL (men) or > 6.0 mg/dL (women), measured via uricase-based enzymatic assay. Survey-weighted logistic regression models were used to evaluate the associations of CircS with gout and hyperuricemia, adjusting for potential covariates. To assess nonlinear correlations, a restricted cubic spline (RCS) analysis was conducted. Sensitivity analysis was performed to test the stability of results. Results The study incorporated a total of 30,157 participants aged 20 years or older, out of which 14,698 were male. After full adjustment, those with CircS had higher odds of gout (OR = 1.34, 95% CI [1.03, 1.73], P = 0.03) and hyperuricemia (OR = 1.25, 95% CI [1.11, 1.41], P < 0.001) compared with individuals without CircS. A gradual increase in serum UA levels was associated with CircS. The RCS curve displays a nonlinear relationship between UA levels and CircS. Sensitivity analyses, including stratified analyses across key covariates and trend tests for CircS scores, consistently demonstrated that the associations of CircS with gout and hyperuricemia remained robust. Conclusion This study identified that CircS was significantly associated with both gout and hyperuricemia in the US general population. The risk of these conditions increased in parallel with rising CircS scores. Elevated UA levels were also associated with a higher incidence of CircS. Given the limitations inherent to the cross-sectional design, further longitudinal studies are required to establish causality and elucidate underlying mechanisms.